Predictors and Components in the Academic Motivation of Nursing Students during the Covid-19 Pandemic in Jordan - Khamaiseh, Abdullah; Al Hadid, Lourance; Barmawi, Marwa; AlAzzam, Manar; Taha, Hana (Jordan Medical Journal, 2022)
Abstract Background: Nursing is a noble profession that aims to care for individuals, families, and communities to achieve optimum health and quality of life. Nurses are the largest constituent of the healthcare team and nursing students’ motivation towards their field of inquiry affects their satisfaction and academic performance. Aim: To examine the academic motivation among nursing students in public universities in Jordan in the context of COVID-19. Materials and Methods: A descriptive cross-sectional study conducted in three public universities in Jordan. A total of 437 nursing students in their second, third, or fourth year of study answered a self-administered online questionnaire. Descriptive and multivariant analysis was conducted using SPSS 24. Results: Academic motivation among students from three public universities was below the averages reported in the international literature. Students’ mean scores on the academic motivation scale knowledge was 90.25 out of 196, and the average mean scores for all subscales were just above the midpoint, except for the extrinsic regulation scale, which was 14.57 out of 30. Students reported higher levels of extrinsic motivation. Conclusions: Educators must focus on nursing students’ need for support and consider the development of a curriculum that strengthens student learning and nurtures their internal and external motivation needs.